Metode Pengajaran Qira’ah - Marwati Marwati (Jurnal Adabiyah: Humanities and Islamic Studies, 2011)
Reading (qira'ah) is a process to find the language. It can be done directly by children (acquisition) to find the first language, and can also be done by adults whose study the second language by formal learning. The teaching-reading method is a system to easily apply the activity relating to the present of subject to find the meaning of the reading text. The purpose of teaching reading is to grow and improve the reading skill which consist of: to recognize the Arabic alphabet or letter symbols and to understand the reading content. In teaching reading, method is appropriated by the kind and the teaching purpose as partial method used to recognize arabic symbols or alphabet which can be compound word, and the analysis method is used to understand reading content by several methods like; reading aloud, strategy of random text, reading guide, reading silent etc.